2003
DOI: 10.1002/clc.4960261007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocardiography in coronary artery disease with a new system in an unshielded setting

Abstract: SummaryBackground: The noninvasive detection of coronary artery disease (CAD) remains a clinical challenge. Magnetocardiography is a completely noninvasive method that permits the registration of cardiac electrical activity at multiple sites in a plane above the chest cage without the need for electrodes. In contrast to the electrocardiogram (ECG) which suffers from boundary effects and a variety of potential artifacts (electrode placement, etc.) the MCG is unaffected by such impediments as the magnetic field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
4
16
0
2
Order By: Relevance
“…They were able to identify STsegment and T-wave changes on MCG of their 12 volunteers during cycling. This idea is supported by similar studies by Hailer et al 14 and Kanzaki et al 15 who were also able to demonstrate increased sensitivity for ischemia by the MCG compared to the ECG in small groups, using either the ST-T interval or QRS waves to diagnose. 13 Their study of 22 healthy volunteers and 44 patients with CAD demonstrated the potential clinical relevance of the ST-T interval for detection of ischemic changes on MCG.…”
Section: Discussionsupporting
confidence: 54%
“…They were able to identify STsegment and T-wave changes on MCG of their 12 volunteers during cycling. This idea is supported by similar studies by Hailer et al 14 and Kanzaki et al 15 who were also able to demonstrate increased sensitivity for ischemia by the MCG compared to the ECG in small groups, using either the ST-T interval or QRS waves to diagnose. 13 Their study of 22 healthy volunteers and 44 patients with CAD demonstrated the potential clinical relevance of the ST-T interval for detection of ischemic changes on MCG.…”
Section: Discussionsupporting
confidence: 54%
“…1C). 19 The present study was performed with a four-channel magnetometer in unshielded location. Most of the patients included in these studies had a normal ECG at rest.…”
mentioning
confidence: 99%
“…Due to the positive results the present study aimed to determine whether LVH changes current density distribution comparable to CAD. The analysis was based on a map classification system that takes the homogeneity of the magnetic field pattern as well as the presence of a dipolar pattern into account [6]. On the one hand, we found a higher frequency of lower map classes as a measure for a more dipolar and homogenous pattern in patients without LVH both in CAD as well as in no CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…From these current density vector maps were generated every 10 ms within the ST-T interval starting with the J-point whereby lead II of the surface ECG served as reference channel. Each of these maps was analyzed automatically by means of a classification system with a scale from 0 (normal) to the classes 1-4 indicating an increasing deviation from the normal direction of the current distribution and from a dipolar pattern [6,7]. For each subject, the relative number of maps per category was determined.…”
Section: Methodsmentioning
confidence: 99%